2021
DOI: 10.1007/s13178-021-00554-1
|View full text |Cite
|
Sign up to set email alerts
|

Why Doesn't the Decriminalisation of Same-Sex Sexuality and Sex Work Ensure Rights? The Legality and Social Acceptance of Transgressive Sexualities in Urban Mozambique

Abstract: Background The dependence on the law to direct people’s behaviour is known for its imperfections, yet it has become a mainstream response to social problems in modern day society. It is also the pathway through which internationally-recognised rights obligations, including sexual rights, are anticipated to diffuse across distinctly different societies. We studied the introduction of new legal standards in Mozambique, with an interest in their ability to promote the rights of lesbian, gay, bisexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Building on the evidence of harms caused by criminalization of consensual adult sex work, which has been documented in a number of studies from both Canada and abroad (Abel, 2014;Armstrong, 2020;Brooks-Gordon et al, 2020;Global Network of Sex Work Projects, 2013;Lutnick & Cohan, 2009), including our own publications on the topic (Benoit et al, 2019b;Benoit et al, 2017), this paper has sought to bring active sex workers' suggestions for other policy changes to the forefront. The views of sex workers are largely absent in sex work law reform (Aantjes et al, 2021;Armstrong & Abel, 2020a;Aroney & Crofts, 2019;O'Doherty, 2011;Levy-Oronovic et al, 2020;van der Meulen, 2011). This knowledge gap has arguably resulted in policy formation that does not address the concerns of active sex workers, or support their occupational health, safety and human rights (Brooks-Gordon et al, 2020;Platt et al, 2018;Sanders et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on the evidence of harms caused by criminalization of consensual adult sex work, which has been documented in a number of studies from both Canada and abroad (Abel, 2014;Armstrong, 2020;Brooks-Gordon et al, 2020;Global Network of Sex Work Projects, 2013;Lutnick & Cohan, 2009), including our own publications on the topic (Benoit et al, 2019b;Benoit et al, 2017), this paper has sought to bring active sex workers' suggestions for other policy changes to the forefront. The views of sex workers are largely absent in sex work law reform (Aantjes et al, 2021;Armstrong & Abel, 2020a;Aroney & Crofts, 2019;O'Doherty, 2011;Levy-Oronovic et al, 2020;van der Meulen, 2011). This knowledge gap has arguably resulted in policy formation that does not address the concerns of active sex workers, or support their occupational health, safety and human rights (Brooks-Gordon et al, 2020;Platt et al, 2018;Sanders et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of the literature, Platt et al (2018) found that criminal laws affecting the sale, purchase, and organization of sex work cause far-reaching harms to sex workers that decrease safety, peer support, and services and increase police harassment. Decriminalizing all areas of sex work reduces harms and improves the health and safety of sex workers by allowing them to organize their work without running afoul of the law, and seek protective services when victimized with less fear of harassment or discrimination, although stigma still remains a significant issue under decriminalization (Aantjes et al, 2021;Abel, 2014;Abel & Ludeke, 2021;Argento et al, 2020;Armstrong & Abel, 2020b;Armstrong & Fraser, 2020;Crago et al, 2021;Easterbrook-Smith, 2020;Jackson & Heineman, 2018;Levy-Oronovic et al, 2020;Platt et al, 2018;Sanders et al, 2020). Global social rights agencies, such as Amnesty International (2016), advocate decriminalization as a harm reduction approach, making it a human right for individuals, who voluntarily decide to do sex work, to have access to similar employment and civil rights as other service workers, and be unfettered by stigma and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is based on empirical case studies in four countries, which were carried out between 2019 and 2021 (for country level analyses please see Aantjes et al, 2021;Freedman et al, 2021;Crankshaw et al, 2021;Chareka et al, 2021). The case studies involved a review of national sex work laws and policies, in-depth and semi-structured interviews as well as focus group discussions (FGDs) with young women aged between 18-24 years on issues related to their sexual and reproductive health and rights (SRHR) 2 .…”
Section: Methodsmentioning
confidence: 99%
“…We had planned to carry out 1 FGD per site but due to COVID-19 restrictions, we could accomplish this for Nampula only. Data collection formed part of a larger country study which included semi-structured interviews on sex work with 16 national key informants and with 78 opinion leaders at community level (further sampling details can be found in Aantjes et al, 2021). The first participants of the study were identified and recruited by the research team, after which recruitment continued within the social network structures of each of these individuals.…”
Section: Peer-reviewed Articlementioning
confidence: 99%
See 1 more Smart Citation